Research on overburden movement laws and spontaneous combustion “three zones” of composite goaf in shallow buried depth and stereo-intersected coal seam group - Dianfu CHEN; Quan NI; Bing WU; Yang LI (Meikuang Anquan)
To thoroughly investigate the effects of coal seam group mining on overburden movement and coal spontaneous combustion risks, this study focuses on the composite goaf of the 12204 and 22206 working faces in Daliuta Huojitu Mine; this study systematically studies the overburden movement and surface subsidence characteristics induced by coal seam group mining and further finds out the risk of coal spontaneous combustion risks in the composite goaf by integrating numerical simulations. Theoretical calculation combining with UAV-based measurements are used to comprehensively assess surface subsidence in the composite goaf. The study employed 3DEC numerical simulation software to simulate the impacts of composite coal seam mining on overburden movement. Simulation results were validated using surface subsidence data, and the Fluent software was utilized to refine the delineation of the spontaneous combustion “three zones” in the composite goaf by incorporating an oxygen consumption function. This facilitated an in-depth analysis of the spatial distribution characteristics of the oxidation zone and its implications for coal spontaneous combustion risks. Theoretical calculations revealed that the maximum surface subsidence in the recompaction zones of the 12204 and 22206 working faces was 3.54 m and 1.06 m, respectively. UAV-based differential elevation measurements indicated that the surface subsidence in the overlapping goaf region reached up to 5 m. Simulated data showed that the surface subsidence coefficient in the overlapping region of the coal seam group mining was 0.24, whereas the coefficient above the coal pillars in the lower coal seam was only 0.12. The surface subsidence caused by coal seam group mining was double that of single-seam mining. Furthermore, after the lower coal seam was mined, the overburden experienced secondary compressive deformation, with the caving angle reduced by approximately 9° compared to the initial deformation. The oxygen field simulation using Fluent demonstrated that the oxidation zone width on the intake side of the lower coal seam was approximately 143 m, while that on the return side was about 50 m. The oxidation zone areas of the upper and lower coal seam floors were 26 676 m2 and 24 003 m2, respectively, indicating a higher risk of spontaneous combustion in the upper coal seam. High oxygen volume fraction zones were primarily concentrated on the intake side and in fracture-developed areas.